Asymptotics of Time Harmonic Solutions to a Thin Ferroelectric Model - Naïma Aïssa; Kamel Hamdache (Abstract and Applied Analysis)
We introduce new model equations to describe the dynamics of the electric polarization in a ferroelectric material. We consider a thin cylinder representing the material with thickness ɛ and discuss the asymptotic behavior of the time harmonic solutions to the model when ɛ tends to 0. We obtain a reduced model settled in the cross-section of the cylinder describing the dynamics of the plane components of the polarization and electric fields.